Sri Lanka : Fourth Post-Program Monitoring Discussion-Press Release; Staff Report; and Statement by the Executive Director for Sri Lanka. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2016)
This paper discusses recent economic developments, outlook, and policies required to stabilize the economy of Sri Lanka. Recent economic developments reflect a more challenging external environment as well as a sharpening of macro-financial imbalances that began emerging late in 2014. Fiscal consolidation has stalled, and public debt is set to rise in 2015. Monetary policy has been on hold since the last rate cut in April 2015, and there appears little room for additional easing. Quick action is needed to reestablish credible policies and restore confidence. Strong fiscal and monetary policies need to be implemented for sustainable economic growth in Sri Lanka.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet